Transformasi Pendidikan Perbatasan: Penguatan Literasi Akademik dan Kesiapan Kuliah Bagi Siswa SMA di Kabupaten Malaka - Saragih, Fernando; Simbolon, Gallex; Wijaya, I Nyoman Wahyu Esa; Leuape, Emanuel Sowe (Jurnal Kelimutu Pengabdian Masyarakat, 2025)
Low academic readiness and limited interest in pursuing higher education remain significant challenges among high school students in Malaka Regency, a border area in East Nusa Tenggara Province. This community service program aimed to strengthen students’ academic literacy and college preparedness through academic literacy training, career guidance, and interest–aptitude assessments based on Holland's RIASEC theory. The implementation involved needs assessment, contextual material development, interactive workshops, simulated college learning experiences, and evaluation using pre- and post-tests. Post-test results indicated a substantial improvement across all indicators, including understanding of the higher education system, academic reading skills, basic academic writing, career awareness, and students’ confidence to pursue college. Active student participation reflected the program's relevance and applicability to their context. Overall, the program had a positive impact on students’ knowledge, motivation, and ability to plan their academic future based on personal strengths and interests. Therefore, this initiative can be recommended as a replicable educational intervention model to support higher education access in other underdeveloped regions.